A Systematic Review of the Impact of ChatGPT at Higher Education Level - Irma Savitri Sadikin; Imam Santosa (Proceeding of the International Conference on Global Education and Learning, 2024)
This systematic review investigates the significant role of ChatGPT in higher education, with a specific focus on its influence on academic writing. Utilizing insights from 17 peer-reviewed articles published between 2022 and 2024, it evaluates ChatGPT's features, advantages, and challenges in assisting both students and educators. ChatGPT enhances efficiency by automating repetitive tasks such as grammar correction, sentence restructuring, and formatting, allowing students to focus on critical thinking and content refinement. Its ability to enhance language, correct grammar, and maintain structural coherence proves especially valuable for non-native English speakers, fostering greater accessibility and fairness in academic writing. Moreover, ChatGPT fosters creativity through brainstorming support, simplifies technical explanations for diverse academic audiences, and enhances iterative learning by providing real-time feedback on coherence, language, and argumentation. The study underscores the risks of bias in AI-generated content and the possibility of worsening educational disparities due to unequal access to advanced AI technologies. Establishing clear institutional policies and ethical guidelines is essential to address these concerns and ensure responsible AI use. The review concludes that ChatGPT is a powerful tool for improving academic writing and learning in higher education. However, its success relies on a balanced integration of AI's capabilities with sound pedagogical practices to uphold academic integrity and encourage independent critical thinking.